2016
DOI: 10.1016/j.rppnen.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Is the COPD assessment test (CAT) effective in demonstrating the systemic inflammation and other components in COPD?

Abstract: Systemic inflammation persists in the stable period of COPD. CRP, one of the inflammation markers, was correlated with the CAT. Further studies are required to confirm the relationship between CAT and biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
10
1
1
Order By: Relevance
“…Chronic Obstructive Pulmonary Disease (COPD) is one of those diseases in which HRQoL is affected and becoming a major environmental and public health issue [1]. Globally, COPD is considered a significant cause of mortality and morbidity across the modern world [2] [3]. COPD is likely to increase in the coming years due to higher smoking prevalence, aging populations in many countries, and the spreading of environmental pollutants [4].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic Obstructive Pulmonary Disease (COPD) is one of those diseases in which HRQoL is affected and becoming a major environmental and public health issue [1]. Globally, COPD is considered a significant cause of mortality and morbidity across the modern world [2] [3]. COPD is likely to increase in the coming years due to higher smoking prevalence, aging populations in many countries, and the spreading of environmental pollutants [4].…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence for this may be inferred from the relatively high average age of the study population, the high proportion of smokers, and the CAT score results: 90% of participants had scores 10. Previous studies have demonstrated associations between increasing CAT score and airflow limitation or COPD severity [53][54][55][56] ; in addition, despite the nonspecific nature of the symptoms described by the CAT, significantly higher scores have been reported in individuals with airflow limitation characteristic of COPD than individuals without, and it has been suggested that the test may prove useful for case finding. 57,58 Data from 2 studies showed that the majority of individuals with airflow limitation have CAT scores > 7 58 ; more than 90% of the participants in the present study met this criterion.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to this aim, the MARKO questionnaire showed a higher sensitivity for early symptoms of future possible COPD than SGRQ or CAT, with high convergent validity correlation with these already validated COPD health status questionnaires. This high convergent validity correlation is also important because it shows specificity for respiratory disorders and could probably mean that it could be associated with already known features of CAT and SGRQ, showing association with many facets of COPD, like underlying inflammation, airway limitation, breathlessness, progression of disease, morbidity, and mortality (11-15). On the other hand, at least for the 18-item version, the results were not influenced by common comorbidities and concomitant treatment.…”
Section: Discussionmentioning
confidence: 99%